Workflow for Visualization of Neuroimaging Data with an Augmented Reality Device. - Karmonik, Christof; Boone, Timothy B.; Khavari, Rose (Journal of Digital Imaging, 2018)
Commercial availability of three-dimensional (3D) augmented reality (AR) devices has increased interest in using this novel technology for visualizing neuroimaging data. Here, a technical workflow and algorithm for importing 3D surface-based segmentations derived from magnetic resonance imaging data into a head-mounted AR device is presented and illustrated on selected examples: the pial cortical surface of the human brain, fMRI BOLD maps, reconstructed white matter tracts, and a brain network of functional connectivity.